2021
DOI: 10.1186/s13018-021-02711-z
|View full text |Cite
|
Sign up to set email alerts
|

Ball heading and subclinical concussion in soccer as a risk factor for anterior cruciate ligament injury

Abstract: Soccer players have a high risk of anterior cruciate ligament (ACL) injury, a potentially career-ending event. ACL rupture has been linked with abnormal neuromuscular control in the lower limb. Additionally, heading the ball with the unprotected head during game play is increasingly recognized as a major source of exposure to concussive and sub-concussive repetitive head impacts. This article provides a hypothesis of potential connection of ACL injury with ball heading in soccer players. The study reviews lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Higher postural control was found to be one of the most influential factors on technical skill performance under the pressure of competitors and rapidly changing situations. In order to enhance branch-specific technical skills and increase the success rate of their performance in the game, it is recommended that balancing training be performed in addition to their use in injury prevention 35 . Due to their strength, these athletes are at risk for brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…Higher postural control was found to be one of the most influential factors on technical skill performance under the pressure of competitors and rapidly changing situations. In order to enhance branch-specific technical skills and increase the success rate of their performance in the game, it is recommended that balancing training be performed in addition to their use in injury prevention 35 . Due to their strength, these athletes are at risk for brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…Future research into injury mechanisms should also consider the contextual factors surrounding the injury to ensure the chaotic complexity of match play is at the forefront of discussion. [114][115][116] CONCLUSION Clearly, strength, neuromotor agility, psychological, and cardiovascular fitness are required for a safe RTP, and authors have suggested that ecological situations used to study these parameters are important to implement. Novel concepts are highlighted regarding assessments for both clinical and field measurement use, which together capture a more complete picture of neuromotor control in the athlete.…”
Section: Is Neuromotor Control the Key?mentioning
confidence: 99%
“…Repeated concussions, relatively common in contact sports, have been recognized as serious medical events that can cause sustained cognitive and psychiatric changes, as well as neurodegeneration ( McKee et al, 2009 ; Prins et al, 2013 ; Greco et al, 2019 ; Zetterberg et al, 2019 ; Kashyap et al, 2022 ). Recently, it has become evident that non-injurious sub-concussive repeated head impacts, such as frequent heading in soccer, may result in acute and chronic neurological effects ( Ashton et al, 2020 ; Kakavas et al, 2021 ; McCunn et al, 2021 ; Sandmo et al, 2022 ). Blast induced traumatic brain injury (bTBI) has been referred to as a hallmark neurological signature in servicemen exposed to blast waves generated by improvised explosive devices (IED) during recent military operations ( Cernak, 2017 ; DePalma and Hoffman, 2018 ;…”
Section: Introductionmentioning
confidence: 99%